Women in Disaster Policy: A Bibliometric Mapping of the Research Literature 2015-2023 - Karima, Nayla (Policy & Governance Review, 2024)
The research regarding women in disaster policy discourse received attention from scholars and policymakers as the current leading international disaster policy had a shortfall in mentioning women's rights. Although many studies have deliberated how women engage with disaster, research that systematically maps how the literature regarding women in disaster policy develops has not yet been conducted. Per the result through the bibliometric mapping, the 58 pieces of literature included by the PRISMA (Preferred Items for Systematic Reviews and Meta-Analyses) framework are clustered into health, environment, economic, and socio-political contexts. The discourse discussion revolves around women's vulnerability, capacity and capability, and strategy and policy initiatives. The study contributes to the literature by mapping the research trajectory regarding women in the disaster risk reduction policy framework following the Sendai Framework for Disaster Risk Reduction 2015-2030 establishment. A recommendation model of the disaster policy framework and prospective research agenda is developed through the study.